MARKETING PERFORMANCE DEVELOPMENT: APPLICATION OF THE CONCEPT OF DIGITAL MARKETING AND MARKET ORIENTATION STRATEGY IN THE MSME SECTOR - Ikramuddin, Ikramuddin; Matriadi, Faisal; Yusuf Iis, Em.; Mariyudi, Mariyudi (RADJA PUBLIKA, 2021)
Changes in consumer behavior require companies to rethink their marketing strategies, especially in the digital marketing era. The Covid-19 pandemic has suppressed the marketing performance of MSMEs in a negative direction, so MSMEs need to improve their marketing strategies towards the concept of digital marketing. This study aims to analyze the role of the digital marketing platform, marketing orientation and entrepreneur orientation on the marketing performance of MSMEs during the Covid-19 pandemic in North Aceh Regency. This research is survey research with a sampling approach, the number of samples used in this study is 131 MSME actors in North Aceh Regency which are determined by purposive sampling. The data were analyzed using the Structural Equational Modeling (SEM) software Amos. Based on a survey of marketing managers and MSME managers, this study shows that MSMEs face various internal and external pressures to adopt digital marketing platforms as a medium to improve their marketing. This can be seen from the low perception of respondents on the influence of the entrepreneurial orientation variable on marketing performance. However, in this case, MSME Marketing Performance is influenced by digital marketing and marketing orientation, each coefficient value for digital marketing is 0.215 and CR 3.387 (P-Value 0.000 < 0.05) and marketing orientation is 0.621 and CR 8.466 (P-Value 0.000 < 0.05). ). The involvement of digital marketing and marketing orientation in MSMEs is expected to increase the company's performance and income. To increase digital marketing engagement, MSME actors who focus on relationship-based interactions with their customers through various digital marketing platforms and on-line buying and selling sites are still expected. This research shows how some companies outside of MSMEs have achieved this. This study makes an important contribution in improving the marketing performance of MSMEs through the relationship of digital marketing platforms, customer orientation and entrepreneurial orientation.